A Phenomenological Study of Scouting-Based Outbound Learning to Strengthen Elementary School Students’ Cooperation and Solidarity - Muh. Khaerul Ummah BK; Hamna; Nurul Hidayah; Moh. Fauzan (Madako Elementary School, 2026)
This study is grounded in the issue of suboptimal development of cooperation and solidarity among elementary school students, which has not been effectively fostered through conventional instructional approaches. The study aims to explore in depth the essential experiences of students participating in scouting-based educational outbound activities using a qualitative phenomenological approach. Data were collected through participatory observation, in-depth interviews, and documentation at SDN 3 Tolitoli, with a focus on group interaction dynamics, student engagement, and the role of supervising teachers. Data analysis was conducted thematically to uncover the meaning of participants’ collective experiences. The findings indicate that structured outbound activities such as collaborative games, knot-tying exercises, marching drills, and stretcher simulations significantly enhance the quality of social interaction, collective responsibility, and collaborative problem-solving skills. The discussion suggests that experiential learning and group dynamics effectively facilitate the internalization of cooperation and solidarity values, as reflected in improved interpersonal communication, mutual trust, role awareness, and team adaptability. The study implies that integrating scouting-based outbound activities serves as a transformative pedagogical approach, offering strong relevance for sustainably strengthening students’ social competencies.